2018
DOI: 10.1002/ange.201800479
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Fast Ion Conduction and Selective Cation Channels for a High‐Rate and High‐Voltage Hybrid Aqueous Battery

Abstract: The rechargeable aqueous metal-ion battery (RAMB) has attracted considerable attention due to its safety,l ow costs,a nd environmental friendliness.Y et the poor-performance electrode materials lead to al ow feasibility of practical application. Ahybrid aqueous battery (HAB) built from electrode materials with selective cation channels could increase the electrode applicability and thus enlarge the application of RAMB.H erein, we construct ah igh-voltage K-Na HAB based on K 2 FeFe(CN) 6 cathode and carboncoate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 34 publications
1
17
0
Order By: Relevance
“…The schematic diagram of the full cell and the ion‐transport mechanism between two electrodes are proposed (Figure S16, Supporting Information). For NiFC‐porous cathode and NaTi 2 (PO) 3 /C anode, it is clearly observed that the dominate insertion ions in K + /Na + electrolyte are K + and Na + , respectively, consisting with recently reported K 2 FeFe(CN) 6 //NaTi 2 (PO) 3 hybrid full‐cells . Figure 6 a shows the galvanostatic voltage profiles of the full‐cell and individual anodes/cathodes at a 10 C rate.…”
Section: Resultssupporting
confidence: 62%
“…The schematic diagram of the full cell and the ion‐transport mechanism between two electrodes are proposed (Figure S16, Supporting Information). For NiFC‐porous cathode and NaTi 2 (PO) 3 /C anode, it is clearly observed that the dominate insertion ions in K + /Na + electrolyte are K + and Na + , respectively, consisting with recently reported K 2 FeFe(CN) 6 //NaTi 2 (PO) 3 hybrid full‐cells . Figure 6 a shows the galvanostatic voltage profiles of the full‐cell and individual anodes/cathodes at a 10 C rate.…”
Section: Resultssupporting
confidence: 62%
“…However, the charge/discharge mechanism and performance of MnO2 is dependent on the particle size and the difference in crystallographic polymorphs (α, β, γ, δ, λ, and amorphous) [22]. In addition, aqueous rechargeable Zn/MnO2 batteries usually exhibit poor stability and restricted energy density due to water splitting in the aqueous electrolytes providing further challenges [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, a high energy density of 69.6 Wh kg −1 calculated on the total mass of active electrode materials could be obtained, which is comparable to or even superior to that of current commercial aqueous batteries (Fig. 11 b) [ 186 ]. Using this strategy for integrating different electrode materials with unique cation selectivity toward metal ions, a high-voltage rechargeable aqueous battery will be realized with a high capacity, remarkable energy density, and considerable capacity retention at a high rate.…”
Section: Sodium-ion Batteriesmentioning
confidence: 99%
“…e Rate performance of the HAB. f Long-term cycling stability of the HAB at the rate of 60 C [ 186 ]. Copyright 2018, Wiley-VCH Verlag …”
Section: Sodium-ion Batteriesmentioning
confidence: 99%